Analisis Pengandalian Persediaan Bahan Baku Kayu Pada Alfa Meubel di Kecamatan Luwuk Selatan, Kabupaten Banggai: Study On Raw Material Inventory Control At Alfa Funiture Company In South Luwuk District Banggai Regency - Rika Yunita Pratiwi; Mastia M Halimu (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2026)
This study aims to analyze the purchasing pattern of raw materials for each order, determine the amount of raw material safety stock that needs to be prepared, and identify the right time to reorder. The results of this study show that by applying the EOQ method, the economical purchase quantity of raw materials in 2025 is 28.45 m³, with an order frequency of 6.29 times and an optimal cycle time for each order of 28.6 days. The safety stock that must be provided is 5.413 m³. Meanwhile, the right time to reorder is when the stock reaches 7,917 m³.